1998
DOI: 10.1111/j.1749-6632.1998.tb10117.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminin Isoforms and Epithelial Development

Abstract: Several different approaches suggest that basement-membrane assembly is important for epithelial development. Basement membranes contain isoforms of collagen IV, proteoglycans, and noncollagenous glycoproteins such as the laminins and nidogens. The expression and role of laminins for epithelial morphogenesis is reviewed. Laminins are large heterotrimeric proteins composed of alpha, beta, and gamma chains. Many major epithelial laminins and their receptors have been identified recently, and the extracellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
11

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 67 publications
(121 reference statements)
4
98
0
11
Order By: Relevance
“…The biologic importance of Ln-1, or proteolytic fragments of it, in inflammatory cell protease production and chemotaxis in vivo is unknown, because Ln-1 is not expressed in most adult tissues (13)(14)(15)(16)(17)(18). Our data indicate that laminin-␣5 derived peptides mediate responses by inflammatory cells, including protease production and chemotaxis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The biologic importance of Ln-1, or proteolytic fragments of it, in inflammatory cell protease production and chemotaxis in vivo is unknown, because Ln-1 is not expressed in most adult tissues (13)(14)(15)(16)(17)(18). Our data indicate that laminin-␣5 derived peptides mediate responses by inflammatory cells, including protease production and chemotaxis.…”
Section: Discussionmentioning
confidence: 85%
“…Peptides containing the sequence SIKVAV located near the C-terminal globular domain of the laminin ␣1 chain induce expression of gelatinase B (gelB/MMP-9) by monocytes/macrophages (6,8), whereas intact Ln-1 does not (9). The biologic importance of cryptic domains in the Ln-1 in vivo is unclear because laminin ␣1, the ␣-chain of Ln-1, is not expressed in most adult tissues (13)(14)(15)(16)(17)(18). This suggests that the laminin in the adult matrix that regulates biological activities likely contains a different laminin ␣-chain.…”
mentioning
confidence: 99%
“…Laminin-1 shows restricted expression that is largely limited to epithelial basement membranes. Laminin-1 is detected in most embryonic tissues during early morphogenesis and remains present as a major epithelial laminin in some adult tissues [2,11-13]. Mice that are deficient in any chain that composes laminin-1 (α1β1γ1) die during the early postimplantation period with the Lama1 -/- phenotype being the mildest of the three genes deleted [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides laminin-1 (α1β1γ1), laminin alpha-1 participates in one additional trimer, laminin-3 (α1β2γ1) [11,27]. Interestingly, except for lama1, all other components of either laminin-1 or -3 were found to be involved in ocular developmental phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…There was one exception, namely the HMEC-1-infected culture where only trace amounts of L36-scFv were detected. Since HMEC-1 cells have been demonstrated to express laminin [26][27][28] and given the fact that the cellular L36-scFv had been found to react with laminin-1 (Fig 3a), it was assumed that substantial amounts of the L36-scFv produced were tightly associated with HMEC-1 cells, thereby leaving only small and therefore undetectable levels of unbound L36-scFv in the supernatant. In summary, these results suggested that a variety of tumor cells were permissive for L36-furin-A and 7A5-furin-A RCR vector infection, and could secrete functional scFvs.…”
Section: Infectivity Of 7a5-scfv-and L36-scfv-encoding Rcr Vectors Inmentioning
confidence: 99%